2020
DOI: 10.1002/acn3.51260
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous truncating variant in CCDC186 in an individual with epileptic encephalopathy

Abstract: Coiled‐Coil Domain Containing Protein 186 (CCDC186) is hypothesized to play an important role in the biogenesis of dense‐core vesicles in neurons and endocrine cells. Biallelic loss‐of‐function variants in the encoding gene CCDC186 have been suggested as a candidate gene for a neurodevelopmental phenotype, but only one patient has been described so far. We report a second patient with a CCDC186‐associated phenotype presenting with developmental delay, epileptic encephalopathy, and failure to thrive. Exome sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Fifteen genes have subsequently reached DGG status. We brie y describe a few exemplary cases below, most of which have already been published in detail elsewhere [43][44][45][46][47][48][49][50][51][52] , and provide a comprehensive list of all patients in the Supplemental Material. In SMARCA5, a gene coding for a chromatin remodeler, we identi ed de novo variants in two patients with neurodevelopmental delay and similar dysmorphic features.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen genes have subsequently reached DGG status. We brie y describe a few exemplary cases below, most of which have already been published in detail elsewhere [43][44][45][46][47][48][49][50][51][52] , and provide a comprehensive list of all patients in the Supplemental Material. In SMARCA5, a gene coding for a chromatin remodeler, we identi ed de novo variants in two patients with neurodevelopmental delay and similar dysmorphic features.…”
Section: Resultsmentioning
confidence: 99%
“…CCDC186 encodes a coiled-coil domain-containing protein that is involved in the maturation of dense-core vesicles (DCVs) at the trans-Golgi network in neurons and endocrine cells [3][4][5]8]. To date, variants in CCDC186 have only been reported in two unrelated individuals presenting with failure to thrive, visual impairment, neurodevelopmental delay, hypotonia, and brain atrophy [14,15]. The patient reported by Brugger et al [15] was clinically characterized in detail, whereas the other one was reported within a large cohort study, and the main phenotypic traits were only summarized in a table format [14].…”
Section: Discussionmentioning
confidence: 99%
“…To date, variants in CCDC186 have only been reported in two unrelated individuals presenting with failure to thrive, visual impairment, neurodevelopmental delay, hypotonia, and brain atrophy [14,15]. The patient reported by Brugger et al [15] was clinically characterized in detail, whereas the other one was reported within a large cohort study, and the main phenotypic traits were only summarized in a table format [14]. Regardless of these descriptions, the association of CCDC186 mutations with this pathologic condition has not been fully established, as functional studies have not been performed in any of the two individuals reported so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 17 candidate genes with high evidence are currently undergoing further investigation, mostly within the framework of international projects. A total of 17 genes (12 associated with autosomal dominant inheritance, 5 with autosomal recessive inheritance) have subsequently acquired DGG status through international cooperation [20][21][22][23][24][25][26][27][28][29][30][31][32] . In comparison with pathogenic variants in previously known disease-associated genes, the present candidate gene set showed a higher proportion of missense variants.…”
Section: Novel Diagnostic-grade Genes (Dgg) and Candidatesmentioning
confidence: 99%